2022
DOI: 10.1016/j.psj.2021.101620
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and molecular epidemiology of fosA3-bearing Escherichia coli from ducks in Shandong province of China

Abstract: The plasmid-borne fosfomycin resistance gene fosA3 has been identified in Escherichia coli ( E. coli ) from various animals but has rarely been reported in ducks. In this study, we investigated the fosA3 prevalence and molecular characteristics of fosA3 -harboring E. coli strains from ducks in Shandong province of China. In 416 E. coli i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 66 publications
0
11
1
Order By: Relevance
“…However, this study revealed that the fosA -like genes in animal-derived Enterobacteriaceae isolates have a general prevalence, with fosA3 (26%) having the highest detection rate. This rate was higher than the previously reported positivity rate for fosA3 in humans, ducks, and pets ( 7 , 10 , 19 ). In addition, all strains containing fosA -like genes in this study exhibited a high-level resistance to fosfomycin (MIC ≥ 512 μg/mL).…”
Section: Discussioncontrasting
confidence: 77%
“…However, this study revealed that the fosA -like genes in animal-derived Enterobacteriaceae isolates have a general prevalence, with fosA3 (26%) having the highest detection rate. This rate was higher than the previously reported positivity rate for fosA3 in humans, ducks, and pets ( 7 , 10 , 19 ). In addition, all strains containing fosA -like genes in this study exhibited a high-level resistance to fosfomycin (MIC ≥ 512 μg/mL).…”
Section: Discussioncontrasting
confidence: 77%
“…Then, ARGs identified in MDR bacterial isolates were tet A (77.1%), sul2 (53.2%), and bla CTX-M (47.3%), which might suggest the widespread usage of tetracycline, sulfonamides, and β-lactams in waterfowl breeding industry. Several studies have reported on the incidence of MDR and ARGs in bacteria, including those by Fashae et al (2021) , Talavera-González et al (2021) , Liu et al (2022a) , and Li et al (2023) . The prevalence of different ARGs in bacteria primarily depends on the frequency of antibiotic use and the level of exposure to various antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the transposon composition, five major fosA3 environment can be classified in Enterobacterales (named type A-E): A) IS 26-fosA3-orf1-orf2- Δ orf3- IS 26 , B) IS 26-fosA3-orf1- Δ orf2- IS 26 , C) IS 26-fosA3- Δ orf1- IS 26 , D) IS 26 -IS Ecp1 - bla CTX-M-14 -ΔIS 903D-fosA3-orf1- Δ orf2- IS 26 , E) IS 26 -IS Ecp1 - bla CTX-M-65 -ΔIS 903D-fosA3-orf1-orf2- Δ orf3- IS 26 ( Figures 9A–E ). The type A is the predominant type, and it is associated to IncF, IncI1, IncN, IncB/O and several untypable plasmids ( Ho et al., 2013 ; Liu et al., 2022 ). FosA3 can be easily co-harbors on the same plasmid with other ESβLs, as bla CTX-M-3 , bla CTX-M-8 , -14 , -55 , -65 and -123 ( Ho et al., 2013 ; Mazé et al., 2014 ; Xie et al., 2016 ; Yang et al, 2016 ; Dantas Palmeira et al., 2018 ).…”
Section: Fosa3mentioning
confidence: 99%
“…Additionally, the authors identified two novel genetic environments surrounding the fosA3 (IS Ecp1 - bla CTX-M-65 -ΔIS 903D -IS 26 - fosA3 - orf1 - orf2 - Δorf3 -IS 26 and IS 26 -IS Ecp1 - bla CTX-M-3 - orf477 - bla TEM-1 -IS 26 - fosA3 - orf1 - orf2 -Δ orf3 -IS 26 ) ( Jiang et al., 2017 ). In E. coli , genomic studies highlighted the occurrence of FosA3 in ST10 ( Seok et al., 2020 ), ST12 ( Hameed et al., 2022 ), ST38 ( Norizuki et al., 2018 ; Hameed et al., 2022 ), ST 46 ( Hameed et al., 2022 ), ST57 ( Hameed et al., 2022 ), ST69 ( Hameed et al., 2022 ; Liu et al., 2022 ), ST95 ( Hameed et al., 2022 ), ST106 ( Seok et al., 2020 ), ST117 ( Fernandes et al., 2018 ; Zhao et al., 2022 ), ST131 ( Galindo-Méndez et al., 2022 ; Hameed et al., 2022 ), ST1193 ( Hameed et al., 2022 ), ST1196 ( Hameed et al., 2022 ), ST2736 ( Wang et al., 2018 ), ST7584 ( Hameed et al., 2022 ), ST10184 ( Hameed et al., 2022 ), ST11350 ( Ewbank et al., 2022 ), ST648 ( Yang et al, 2016 ), ST156 ( Xie et al., 2016 ). The occurrence of plasmid-mediated fosA -like genes turns out to be worrying in ST131 clone due to its virulence and pathogenic features ( Forde et al., 2019 ; Galindo-Méndez et al., 2022 ; Hameed et al., 2022 ).…”
Section: Fosa3mentioning
confidence: 99%
See 1 more Smart Citation